If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 1 = -13 Reorder the terms: 1 + 5y = -13 Solving 1 + 5y = -13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5y = -13 + -1 Combine like terms: 1 + -1 = 0 0 + 5y = -13 + -1 5y = -13 + -1 Combine like terms: -13 + -1 = -14 5y = -14 Divide each side by '5'. y = -2.8 Simplifying y = -2.8
| 1.31+17.3q=17.2q | | 14=v+10 | | y^4-8y^3+16x^2=0 | | 17.7s=15s-14.85 | | 6x-5y+9=0 | | 4.79+13.6t=6.2+13.7t | | (1+z+z^2+8)/(z+1+8-z+z^2-7z-8) | | -15-4k=-14k+9k+1 | | -8f=16-7f | | 4+12m-2=7m+38-4m | | 16-23= | | 9b-20-14b=13+6b | | 0.8(x-100)=450.00 | | -4(m+1)=-2(m+7) | | 10+9-c=-9+3c | | 5-2*7/2 | | -7-7q=-7-9q | | n/8+4=6 | | 5b^2-34b+24=0 | | x/12=8 | | 5-2*-7/2 | | n/2+4=6 | | 6+d=-10-d | | 17-63= | | x^3-8x^2+4x-32=0 | | n/8+5=10 | | -5-2v=-7v | | 3x+3x+3x=198 | | 6(5-4r)=6(4-5r) | | (4/(x+4))-(3/(x-4))=(2x/((x^2)-16)) | | 10+5v=7v-10 | | 6s+5s=-77 |